Path Analysis and Health Belief Model on the Association between Education and Cadre Performance in Tuberculosis Control in Baki Community Health Center, Sukoharjo, Indonesia - Dhian Nurayni Sulistyo Ningrum; Bhisma Murti; Ruben Dharmawan (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: The new cases of tuberculosis in 2014 as many as 9.6 million. There are 6 million cases reported findings. The efforts to increase the number of case finding through cooperate community and community health workers. This study aimed to analyze the association of education and health belief model with a performance of cadres in tuberculosis control.Subjects and Method: This was an observational analytic with a cross sectional design. This was conducted in community health center of Baki, Sukoharjo, Indonesia, in April 2016. A total of sample was 90 subjects were selected by random sampling. The data collection used questionnaire. The data were analyzed using path analysis.Results: There was no relationship between education and the performance of cadres in tuberculosis control cases through the perception of vulnerability, perceived seriousness, perceived benefit, perceived barriers and self-efficacy. There was a direct positive relationship between the perception of vulnerability to the performance of cadres in tuberculosis control cases (b = 3.35; 95% CI= 1.43 to 5.27; p=0.001), seriousness (b=2.21; 95% CI=0.43 to 3.9; p = 0.015), benefits (b= 2.11; 95% CI= 0.42 to 3.80; p = 0.014), self-efficacy (b = 2.04; 95% CI= -0.01 to 4.09; p = 0.051), the impulse to act (b = 1.64; 95% CI= 0.06 to 3.22; p= 0.042) with the performance of cadres in the control of tuberculosis cases. There was a direct negative relationship between perceptions of barriers to the performance of cadres in tuberculosis control (b=-4.54; 95% CI= -7.56 to - 1.52); p = 0.003).Conclusion: There is indirect relationship between education and performance of cadres in tuberculosis control cases through the perception of vulnerability, seriousness, benefits, barrier and self-efficacy. There is a direct relationship between construct of health belief model with the performance of cadres in tuberculosis control cases.Keywords: path analysis, education, health belief model, the performance of cadres, tuberculosisCorrespondences: Dhian Nurayni. Sulistyo Ningrum. Faculty of Public Health, Sebelas Maret University, Surakarta. Email: dhiannuraynis@gmail.comJournal of Health Policy and Management (2016), 1(1): 38-43https://doi.org/10.26911/thejhpm.2016.01.01.06